Evaluasi produksi hijauan sorghum bijian kedele yang ditanam tumpangsari - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Field plots were established in three replicates of randomized complete block design to evaluate production and chemical composition values of intercropped. In Experiment 1 (1988), crops of grain sorghum DeKalb-42Y (SB), soybeans Williams-82 (KW) and Pershing (KP), and intercrops SBKW and SBKP were seeded in 76 cm (A), 38 cm (B), or 15 cm drilled (C). The plots were harvested when the SB reached late-dough stage kernel maturity. Dry matter (DM) production was the highest (P.. Kata kunci: monokultur, tumpangsari, imbangan kesetaraan lahan